Закрытый БИОС при переломах дистального отдела диафиза плечевой кости - Яцун, Е. В.; Трашков, В. Д.; Ивченко, Д. В.; Москальков, А. П.; Кирпиченко, С. Ф.; Yatsun, E. V.; Trashkov, V. D.; Ivchenko, D. V.; Moskalkov, A. P.; Kyrpychenko, S. F.; Яцун, Євген Володимирович; Івченко, Дмитро Валерійович; et al. (К. : Юстон, 2018)
Цель работы: апробация и внедрение методики закрытого БИОС при дистальных внесуставных переломах плечевой кости в условиях отделения травматологии с койками политравмы КУ ГКБЕ и СМИ г. Запорожья. Aim of the study: Approbation and implementation of closed IM nailing in case of extra-articular distal humeral fractures in premises of trauma care department with polytrauma beds of Zaporizhzhia Extreme and Emergency Medical Center, Ukraine.
Closed im nailing of distal humeral diaphysis fractures
Keywords: перелом; плечевая кость; закрытая репозиция; антеградный остеосинтез; fracture; humeral bone; closed reposition; antegrade osteosynthesis